IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VII DI SMP NEGERI 2 JOMBANG - Rodiah, Fatma; Arini, Aida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research intends to evaluate how the Merdeka of curriculum is applied inside the Islamic faith Educations lesson at SMP Negeri 2 Jombang and its effects on the academic performance of seventh grade students the study’s empharish is on the lesson plans crafted by educations, the progression in students’ academic achievements, and how the curriculum aids andhancing the quality of education. A qualitative method with a case study framework is used for this research. Data was gathered via obsevasion, detailed interviews and document reviews. The analisis involved reducing data, presenting it, and drawing conclusions, while the credibility of the findings was guaranteed through varied source comparisons. The findings demonstrate how the Merdeka Curriculum is being used in Islamic Religious Education involves linked phases of planning, delivery, and assessment. This application supports the growth of students' learning results across cognitive, emotional, and physical areas. Additionally, learning opportunities that include discussion, presentations, and hands-on activities improve students' comprehension, confidence, communication abilities, and teamwork. Consequently, implementing the Merdeka Curriculum at this institution fosters a more engaging, relevant, and student-focused method for Islamic Religious Education that meets the needs of learners.